2014
DOI: 10.1016/j.tws.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate response of stainless steel continuous beams

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 21 publications
2
65
0
Order By: Relevance
“…On the basis of the findings, revised slenderness limits for cross-section classification [24] and new effective width formulae for slender sections [15] have been proposed. Theofanous et al [25] conducted two-span continuous beam tests on austenitic and duplex stainless steel sections to enable the influence of moment redistribution within statically indeterminate beams to be examined. As highlighted by previous researchers, the general codified approach of limiting the design stress to the 0.2% proof stress, and ignoring the pronounced strain hardening exhibited by stainless steels can lead to greatly underestimated cross-sectional resistances.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the findings, revised slenderness limits for cross-section classification [24] and new effective width formulae for slender sections [15] have been proposed. Theofanous et al [25] conducted two-span continuous beam tests on austenitic and duplex stainless steel sections to enable the influence of moment redistribution within statically indeterminate beams to be examined. As highlighted by previous researchers, the general codified approach of limiting the design stress to the 0.2% proof stress, and ignoring the pronounced strain hardening exhibited by stainless steels can lead to greatly underestimated cross-sectional resistances.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when more ductile stainless steel families, such as austenitic and lean duplex, are considered, accurate ultimate capacity estimations are obtained through plastic design methods, and CSM for indeterminate structures provides the best predictions of the collapse loads, as demonstrated in [4] and [7]. Therefore, some additional tests and parametric studies on stockier cross-sections are crucial for extending this study to ferritic stainless steel grades.…”
Section: Assessment Of Design Methods and Discussionmentioning
confidence: 99%
“…In order to predict accurately the collapse loads of stocky stainless steel continuous elements, considering moment redistribution and strain hardening, Theofanous et al [4] assessed the applicability of the new design method developed by Gardner et al [7], the CSM for indeterminate structures. The method assigns the full CSM cross-sectional resistance to the critical plastic hinge and allows a degree of strain hardening for the rest of the hinges.…”
Section: New Design Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the importance of moment redistribution in indeterminate aluminium alloy structures is considered herein through the study of two-span continuous beams. Theofanous et al [14] reported that when considering moment redistribution in stainless steel continuous beams, the design capacities were found to be improved by around 10% and offer more accurate prediction of the test response. However, although structural design guidance is widely available for aluminium alloys, global plastic design is generally not permitted in international specifications such as the Aluminium Design Manual [15] and Australian/New Zealand Standards [16].…”
Section: Introductionmentioning
confidence: 99%